2022
DOI: 10.1097/iio.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Treatment for Symptomatic Vitreous Floaters: A Review

Abstract: Symptomatic floaters are those that affect daily life and decrease qualityof-life (QOL) for a duration of at least 3 months. 8 Patients typically complain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Although a few patients reported that their floaters got worse after receiving Nd:YAG laser vitreolysis [ 23 ], this in vivo study found that the laser vitreolysis therapy did not result in the development of any new floaters. Nguyen et al [ 24 ] also reported that the vitreous echo density of Nd:YAG-treated eyes was 23% less than that of untreated eyes with vitreous floaters.…”
Section: Discussionmentioning
confidence: 83%
“…Although a few patients reported that their floaters got worse after receiving Nd:YAG laser vitreolysis [ 23 ], this in vivo study found that the laser vitreolysis therapy did not result in the development of any new floaters. Nguyen et al [ 24 ] also reported that the vitreous echo density of Nd:YAG-treated eyes was 23% less than that of untreated eyes with vitreous floaters.…”
Section: Discussionmentioning
confidence: 83%
“…In 1993, Tsai et al [14] introduced YAG laser vitreolysis for treating oaters. Subsequently, Shah et al [4] were the rst to evaluate the safety and e cacy of this treatment in a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…With aging, adhesions between the posterior vitreous gel and the retina weaken, leading to a posterior vitreous detachment. This, in combination with liquefaction of the vitreous gel, can lead to clinically significant vitreous floaters [2,5]. Vitreous floaters may be symptomatic and characterized as dark spots or shadows in the vision.…”
Section: Introductionmentioning
confidence: 99%